2002
DOI: 10.17796/jcpd.26.1.6470j6777267w163
|View full text |Cite
|
Sign up to set email alerts
|

Primary triple teeth: histological and CT morphological study of two case reports

Abstract: The macromorphology and micromorphology of two specimens of primary triple teeth using histological and CT analysis approach is analyzed. A single morphological pattern of triple teeth has been found and described: three nearly separate crowns with three separate pulp chambers, and three joined roots with three connected root canals. The characteristic triple teeth appearance occurred because a labial supernumerary tooth is the junction element between two teeth of normal series: the central incisor on the mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…[20] Six cases (of available data for 13 cases) showed absence of the corresponding succedaneous teeth. [91015161920] In the present case, there is agenesis of left maxillary permanent lateral incisor.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…[20] Six cases (of available data for 13 cases) showed absence of the corresponding succedaneous teeth. [91015161920] In the present case, there is agenesis of left maxillary permanent lateral incisor.…”
Section: Discussionmentioning
confidence: 63%
“…[5] Only one study with computerized tomography (CT) description of triple tooth that describes a single morphological pattern of three nearly separate crowns with separate pulp chambers and three joined roots with three connected root canals. [16] Only three reports provided histological findings of triple teeth cases and Aguilo et al . reported that the histological findings were similar to the CT findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malformation under this category includes gemination, fusion and concrescence also known as twinned, connated, double, or triple teeth [3]. The term triple tooth is used to describe a rare dental abnormality in which three primary teeth appear to be joined which have been considered the result of fusion or gemination of teeth [4]. The first such case was reported by Bennett back in year of 1887 followed by Sprawson in year 1931.…”
Section: Discussionmentioning
confidence: 99%